2018
DOI: 10.1016/j.biosystems.2017.12.011
|View full text |Cite|
|
Sign up to set email alerts
|

Slime mould: The fundamental mechanisms of biological cognition

Abstract: The slime mould Physarum polycephalum has been used in developing unconventional computing devices for in which the slime mould played a role of a sensing, actuating, and computing device. These devices treated the slime mould as an active living substrate, yet it is a self-consistent living creature which evolved over millions of years and occupied most parts of the world, but in any case, that living entity did not own true cognition, just automated biochemical mechanisms. To "rehabilitate" slime mould from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 163 publications
(257 reference statements)
1
47
0
1
Order By: Relevance
“…An understanding of this phenomenon in simpler models may advance the decoding efforts in neuroscience, which also seeks to understand how behavioral information is stored in living tissue. There are perhaps scale-invariant and substrate-indpendent principles of learning and memory that extend to all cognitive system that can be deduced using this simple model organism (Baluška and Levin, 2016;Friston et al, 2015;Pezzulo and Levin, 2015;Vallverdu et al, 2018;Yokawa and Baluška, 2018). Moreover, measurement of physical properties of the environment is an important but poorly-understood aspect of metazoan morphogenesis, including for example the biomedically important feedback loops that allow cells in a regenerating organ or remodeling structure to determine how to grow and when to stop based on large-scale properties of the real-time anatomy (Butler et al, 2009;Levin and Martinez Arias, 2019;McLaughlin and Levin, 2018;Whited and Levin, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…An understanding of this phenomenon in simpler models may advance the decoding efforts in neuroscience, which also seeks to understand how behavioral information is stored in living tissue. There are perhaps scale-invariant and substrate-indpendent principles of learning and memory that extend to all cognitive system that can be deduced using this simple model organism (Baluška and Levin, 2016;Friston et al, 2015;Pezzulo and Levin, 2015;Vallverdu et al, 2018;Yokawa and Baluška, 2018). Moreover, measurement of physical properties of the environment is an important but poorly-understood aspect of metazoan morphogenesis, including for example the biomedically important feedback loops that allow cells in a regenerating organ or remodeling structure to determine how to grow and when to stop based on large-scale properties of the real-time anatomy (Butler et al, 2009;Levin and Martinez Arias, 2019;McLaughlin and Levin, 2018;Whited and Levin, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Recently it is emerging that all cells [25] demonstrate basal cognition [8,14,16,23,2633]. Indeed, it has been argued that life should properly be defined through the property of self-referential cognition [31,34].…”
Section: The Cell In the 21st Centurymentioning
confidence: 99%
“…Indeed, it has been argued that life should properly be defined through the property of self-referential cognition [31,34]. Furthermore, recent advances have also revealed that neuronal aspects and cognitive capacities are valid concepts for unicellular organisms too [14,16,22,35]. Even bacteria show sensory complexity and sensory-motor circuits between plasma membrane-based sensors and correspondent motor responses of their flagella modulated by previous experiences [14,36].…”
Section: The Cell In the 21st Centurymentioning
confidence: 99%
See 2 more Smart Citations